2001
DOI: 10.1093/nar/29.2.362
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Xenopus laevis CCAAT-enhancer binding protein alpha gene promoter demonstrates species-specific differences in the mechanisms for both auto-activation and regulation by Sp1

Abstract: Transcription factors belonging to the CCAAT-enhancer binding protein (C/EBP) family have been implicated in the regulation of gene expression during differentiation, development and disease. Autoregulation is relatively common in the modulation of C/EBP gene expression and the murine and human C/EBPalpha genes have been shown to be auto-activated by different mechanisms. In the light of this finding, it is essential that autoregulation of C/EBPalpha genes from a wider range of different species be investigate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
38
0
2

Year Published

2001
2001
2010
2010

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(41 citation statements)
references
References 36 publications
1
38
0
2
Order By: Relevance
“…The amplification was carried out using the high fidelity Pwo DNA polymerase to minimize PCR-generated mutations (40,41), and this was confirmed by sequencing. The amplification product (ϳ530 bp) was purified, digested with BamHI and EcoRI, and subcloned into the pcDNA3 vector that had been previously digested with the same enzymes.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The amplification was carried out using the high fidelity Pwo DNA polymerase to minimize PCR-generated mutations (40,41), and this was confirmed by sequencing. The amplification product (ϳ530 bp) was purified, digested with BamHI and EcoRI, and subcloned into the pcDNA3 vector that had been previously digested with the same enzymes.…”
Section: Methodsmentioning
confidence: 99%
“…The recombinant protein was labeled with [ 35 S]methionine (40 Ci) to aid detection. Nuclear and whole cell extracts were prepared essentially as described previously (12,15,16,40,42). Protease inhibitors (0.5 mM phenylmethylsulfonyl fluoride, 1 g/ml pepstatin A, 10 g/ml aprotinin, 10 g/ml I-S soybean trypsin inhibitor) and DTT (0.5 mM) were added to all buffers before use.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…We tested whether xDnmt1 can repress the activation of a minimum promoter that has four copies of the xSp1-binding site driving luciferase expression (p4xSp1-Lucif) (Kockar et al, 2001). Relative induction by xSp1 is reduced by 55% in the presence of…”
Section: Xdnmt1p Is a Transcriptional Repressor And Can Be Localisedmentioning
confidence: 99%
“…Thus, direct binding of the C/EBP-␣ protein to the promoter of the C/EBP-␣ gene is not required for autoregulation (Timchenko et al, 1995). Studies with the Xenopus laevis C/EBP-␣ promoter showed that, in contrast to the human promoter and in common with the murine gene, the xenopus C/EBP-␣ promoter was subject to direct autoregulation (Kockar et al, 2001).…”
Section: Tissue-specific and Species-specific Autoregulation Of The Cmentioning
confidence: 99%